Health-related quality of life among patients with acute ischemic stroke and large vessel occlusion in the PROTECT-MT trial - Renjun Gu; Hongjian Shen; Lei Chen; Fang Shen; Lei Zhang; Zifu Li; Pengfei Xing; Weilong Hua; Yongxin Zhang; Yongwei Zhang; Zhenlin Wang; Jianmin Liu; et al. (Journal of Patient-Reported Outcomes, 2026)
Abstract Background and purpose The balloon guide catheter may improve technical aspects of endovascular thrombectomy (EVT) for acute ischemic stroke (AIS) with large vessel occlusion, but the parent PROTECT-MT trial did not show better clinical outcomes with balloon guide catheter use. Whether these clinical findings are reflected in patient-reported health-related quality of life (HRQoL) remains uncertain. Methods In this multicenter, open-label, blinded-endpoint trial across 28 hospitals in China, 329 patients with anterior circulation large vessel occlusion were randomized 1:1 to EVT with a balloon guide catheter or a conventional guide catheter. HRQoL was assessed cross-sectionally at 90 days using the EuroQol 5-dimension 5-level (EQ-5D-5L) descriptive system and the Chinese value set to derive EQ-5D-5L index values; disability was assessed using the modified Rankin Scale (mRS). Quantile regression and logistic regression models examined treatment effects on the EQ-5D-5L index and its five domains, with prespecified interactions by age and gender. Sensitivity analyses excluded deaths and imputed missing values using truncated regression. Results HRQoL at 90 days was lower with balloon guide catheter versus conventional guide catheter use (median EQ-5D-5L index, 0.27 vs. 0.73), with the clearest adjusted contrast observed among patients aged 60–79 years (adjusted difference − 0.27; 95% CI -0.51 to -0.03). When deaths were excluded, the difference in EQ-5D-5L index between groups was markedly reduced. In exploratory domain-level analyses, balloon guide catheter use showed descriptive worsening in self-care, usual activities, and pain/discomfort, and a nominally higher odds of reporting no anxiety/depression (adjusted odds ratio 2.15; 95% CI 1.13–4.11). HRQoL strongly correlated with mRS (Spearman ρ -0.90), and the negative association between severe disability and HRQoL was greatest among older patients. Conclusions Balloon guide catheter use during EVT was not associated with a 90-day HRQoL advantage and was associated with worse EQ-5D-5L index among patients aged 60–79 years, although the difference diminished after excluding deaths. Domain-specific findings, particularly for anxiety/depression, should be interpreted cautiously given multiplicity and the open-label design. These findings support integrating HRQoL endpoints with traditional disability scales and provide no patient-reported outcome support for routine balloon guide catheter use in AIS due to large vessel occlusion.